A contemporaneidade da Nova Atlântida (1627) de Francis Bacon (1561-1626): contribuições para a análise da categoria técnica na perspectiva do saber geográfico - Nascimento, Sandra do (2010)
The technique concept is directly related to Geography while represents empirically the human abilities to organize, transform and sometimes overcome the nature. Thus, with ample geographic content was present in the construction of this science, since Paul Vidal de La Blache with his way of life, passing by Max Sorre, and currently recognized in Milton Santos, through his Space conception. From the concept of technical-scientific-informational environment, founded by Milton Santos, we search to deconstruct the technical category, researching in the history of western thought, the contributions from different authors to the evolution of this category, in order to understand the concept disseminated in Geography. It's the technique who organize and create the geographic space, through the action of man s work, while inseparable categories in the act of nature production. From this presupposed, we indentify in Francis Bacon the first philosophic reflection that emphasize the role of technique on the nature transformation, like was understood by Geography. It s important to emphasize, that in development of humanism renaissance we found the first ideas to understand the technique as important instrument to be between the relationship of Man and Nature. However, it s in empirical Francis Bacon s philosophy that these ideas, that promotes by the first time the modern sense of progress, gain space and all scientific-methodological basis, showing the modern world to a known technical-scientific, with a major objective of control nature to provide a good service to mankind. From Christian religion's morality, Francis Bacon makes a knowledge project, named Instauratio Magna, and through which he intended to launch the basis of a new scientific investigation method, that rip off the scientific knowledge from the monotony of scholastics theories and all the rhetorical that involved the investigation of nature. The troubled life of politics man was divided with an incontestable interesting by the nature of modern science, in terms of a true revolution of scientific method. So, made the foundations of modern scientific project, Francis Bacon left his last work: New Atlantis, presenting the scientific possibilities of a State organized by the science, through its inductive method. Through the projection of a utopian space, Francis Bacon historically anticipated himself, building a modern tale in which envisions the new spatiality, the new relations between man and nature; and without refers to the Geography raised the technique as a possibility for changing the world, as one of the main pillars of construction of modern geographic space.